Public administration in the field of national security: Updating content during martial law - Ківалов, Сергій Васильович; Ківалов, С. В.; Кивалов, Сергей Васильевич; Kivalov, Serhii V. (Universidad de la Amazonia, 2023)
The article examines the model of public administration in the field of national security that meets the requirements of martial law. The purpose of the study is to determine the format of the existing public administration in the national security sector, taking into account the challenges of the legal regime of martial law by solving such research tasks as outlining the essence of public administration in the field of national security; research of subjects endowed with administrative powers in the field of national security; determination of the directions of transformation of public administration in the specified area. The research methods are the method of analysis, the method of observation and study of documents, the method of comparison, the method of modeling, and logical methods. As a result of the conducted research, the expediency of Ukraine takinginto account the directions of reforming managerial influence on public relations in the field of national security, which are recognized at the level of the European Union, is substantiated. As a condition for the implementation of the necessary changes in the regulation of the security sphere, it is separated from the sphere of defense and the introduction of appropriate changes to the Law of Ukraine "On National Security". The specifics of the institutional support of social relations in the field of national security are identified and the directions for the implementation of the proper doctrine of national security are outlined.

У статті досліджено модель публічного адміністрування в сфері національної безпеки, що відповідає вимогам воєнного стану. Метою дослідження є визначення формату наявного публічного адміністрування в секторі національної безпеки з урахуванням викликів дії правового режиму воєнного стану шляхом вирішення таких науково-дослідних завдань, як: окреслення сутності публічного адміністрування в сфері національної безпеки; дослідження суб’єктів, що наділені владно-розпорядчими повноваженнями в сфері національної безпеки; визначення напрямів трансформації публічного адміністрування в означеній сфері. Методами дослідження є: метод аналізу, метод спостереження та вивчення документів, метод порівняння, метод моделювання, логічні методи. В результаті проведеного дослідження обґрунтовано доцільність врахування Україною напрямів реформування управлінського впливу на суспільні відносини в сфері національної безпеки, яких визнано на рівні Європейського Союзу. В якості умови втілення необхідних змін при регулюванні безпекової сфери є її відмежування від сфери оборони та внесення відповідних змін до Закону України «Про національну безпеку». Виявлено специфіку інституційного забезпечення суспільних відносин в сфері національної безпеки та окреслено напрями втілення належної доктрини національної безпеки.
Kivalov S. Public administration in the field of national security: Updating content during martial law / S. Kivalov // Amazonia Investiga. – V. 12 (65). – Universidad de la Amazonia, 2023. – P. 68-76.
Keywords: public administration; martial law; special period; national security; national identification; публічне адміністрування; воєнний стан; особливий період; національна безпека; національна ідентифікація; Research Subject Categories::LAW/JURISPRUDENCE